Respuesta :

caylus
Hello,

5x^3-6x²-59x+12=5x^3-x²-5x²+x-60x+12
=x²(5x-1)-x(5x-1)-12(5x-1)
=(5x-1)(x²-x-12)
=(5x-1)(x²+3x-4x-12)
=(5x-1)(x(x+3)-4(x+3))
=(5x-1)(x+3)(x-4)

zeros are  -3,4,1/5

Given function : [tex]f(x)=5x^3-6x^2-59x+12.[/tex]

[tex]\mathrm{Factor\:}5x^3-6x^2-59x+12[/tex]

Splitting terms to factor it out.

[tex]5x^3-x^2-5x^2+x-60x+12[/tex]

Making it into groups

(5x^3-x^2) + (-5x^2+x) + (-60x+12)

Factoring out GCF of each group.

[tex]x^2(5x-1)-x(5x-1)-12(5x-1)[/tex]

[tex]=(5x-1)(x^2-x-12)[/tex]

Factoring x^2-x-12 into (x+3)(x-4)

[tex](5x-1)(x^2-x-12) = (5x-1)(x+3)(x-4)[/tex]

Applying zero product rule.

5x-1 =0

x+3=0 and

x-4= 0

On solving

x = 1/5 , x=-3 and x=4.

Therefore, zeros of the given function are [tex]x=-3,\:x=4,\:x=\frac{1}{5}[/tex].